Expression analysis of transcript and protein markers that are related to agar yield and gel strength in Gracilaria changii (Rhodophyta) - Lim, Yi Yi; Lee, Wei Kang; Lim, Phaik Eem; Phang, Siew Moi; Leow, Adam Thean Chor; Namasivayam, Parameswari; Abdullah, Janna Ong; Ho, Chai Ling (Elsevier, 2019)
The supply of agar as an important gelling and thickening agent in various industrial applications depends heavily on harvesting of natural seaweed resources and seaweed farming. To facilitate the selection of good seaweed source with higher agar yield and stronger gel strength, accurate and rapid screening method using molecular markers is necessary to replace the tedious, laborious and time-consuming conventional method which involves agar extraction and gel analysis. In this study, we characterized the expression of a number of algal transcripts and proteins from an agar producing seaweed, Gracilaria changii with the aim to identify potential markers for agar yield and gel strength. In total, 15 candidate transcripts that are directly or indirectly related to putative agar biosynthetic pathway were identified based on literature search. The transcript abundance of 4 and 11 of these candidates were found to be significantly (P < 0.05) correlated to the agar yield and gel strength of six G. changii samples, respectively. Among these marker genes, the transcript levels of GcFBPA and GcGALE have the highest linear correlation to both agar yield and gel strength. The protein abundance of GcFBPA and GcGALE was further examined on 13 G. changii samples and was found to have highly significant (P < 0.01) correlation to agar gel strength and agar yield, respectively. GcFBPA and GcGALE may have good potential to be used for molecular screening of yield traits and gel quality of G. changii at both RNA and protein levels.